APLIKASI RANSUM BERBASIS ECENG GONDOK SEBAGAI UPAYA UNTUK MENINGKATKAN PERFORMAN ENTOG DAN PENDAPATAN PETERNAK DI KELURAHAN TONJONG MAJALENGKA - Dini Widianingrum; Oki Imanudin; Rachmat Somanjaya (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Muscovy duck is a meat-producing waterfowl that is mostly kept by the community, especially in rural areas. The high interest in raising muscovy duck is influenced by the fast growth, the meat is liked, and it is easy to maintain. Obstacles to raising muscovy duck include high consumption of muscovy duck rations so that production costs are also high. As a result, the income of farmers is reduced. The solution, among others, is to look for alternative feed ingredients that are cheap, easy to obtain, and do not compete with other livestock, for example water hyacinth. Water hyacinth is a plant that is easy to grow in water areas as weeds and waste from rice fields, fish ponds, and lakes. The use of water hyacinth as feed for mutton has various advantages, including high nutrient content, cheap, available, and environmentally friendly. The village of Tonjong Majalengka has the Cibudug river which flows all year round. The banks of the Cibudug river are very good for raising squid in the fish pond, which is overgrown with water hyacinth. Very good potential as a center for cattle breeding which is rich in feed sources. The purpose of community service is to apply water hyacinth-based rations as an effort to improve the performance of mutton and the income of farmers. The ingredients for the muscovy duck ration are water hyacinth and fine bran. Making rations using the square method. The method of community service is carried out by demonstration plots, counseling and continuous coaching for farmers and youth organizations in the Tonjong sub-district. Based on the results of the counseling, it was found that the goat breeders had the knowledge and practice of applying water hyacinth-based shrimp rations. In conclusion, water hyacinth is good to be used as a ration for muscovy duck.